The extent of compliance and implementation of R.A. 6966 among academic librarians in Region III - Paez, Leonila S.; Sison, Josephine C.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
This study was aimed at determining: (1) the profile of the librarian-respondents in terms of sex, age, designation, years in service, eligibilities and their socio-economic status; (2) the educational training and status of the respondents; (3) the educational qualifications of the librarians as prescribed by the R.A. 6966; (4) the problems of non-licensed librarians toward compliance with R.A. 6966; and (5) the extent of complicance with, and implementation of R.A. 6966 among academic librarians of Region III. Data and relevant information were obtained by means of a set questionnaire utilizing Likert Scales and personal interviews. One hundred five (105) librarians in-charge of libraries of higher education institutions (HEIs) constituted the respondents of the study.
The socio-demographic characteristics of the respondents were determined from the obtained data where the total frequency of responses were taken for the following variables: age, sex, length of service, civil status, designation, eligibilities, educational attainment, membership in library association, conferences, seminars, workshops attended, and special skills. Monthly salaries of librarian-respondents were determined where mean was computed. Other data gathered were subjected to statistical procedure such as frequency, percentage, ranking and averaging.
Finding of this study revealed that only 51 of the 105 academic librarians have licensed, the academic librarians are mostly female; 31-40 years of age; graduates of baccalaureate degrees in different subject fields and continue to improve educationally by enrolling in courses leading to post graduate degrees; hold different position/titles; members of national as well as regional/local library associations, and skilled in library administration & supervision, cataloguing & classification, acquisitions and indexing & abstracting.
Majority of the librarians 43 (40.94 percent) have been in their present designations from 1-5 years. Majority 14 or 25.93 percent of unlicensed librarian-respondents did not give their reasons/problems with regard to non-compliance with R.A. 6966; followed with 11 or 20.37 percent have no eligibility; 8 (5.56 percent) cited lack of units in library science and not yet eligible prior to the time when R.A. 6966 was approved. By using Likert Scales with an overall average of 2.15 with verbal description of "Adequate" the extent to which R.A, helped respondents in different areas of their work as librarian and information professional. With the total weighted average of 1.67 with verbal description of "Always" show that there is a significant relationship in the performance of the respondents to the extent of compliance and implementation of R.A. 6966. In short, the R. A. 6966 gives the librarians permanent, decent profession.
On the basis of the findings and conclusions, the recommendation of full implementation and compliance with the Philippine Librarianship Act is a must for all librarians in the country. Only professional licensed librarians should be assigned to work in the library pursuant to R.A. 6966.
Computer print out.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: College librarians -- Certification -- Philippines -- Central Luzon; College librarians -- Legal status, laws, etc. -- Philippines